Peranan Problem Based Learning dalam Peningkatan Mutu Pembelajaran di Sekolah Dasar - Heny Ariyanti (RESEARCH FAIR UNISRI, 2021)
The research aims at describing the result of analyzing previous studies about the implementation of Problem based Learning at elementary schools in Indonesia and abroad. They type of research is library research. The techniques in collecting the data used document analysis that consists of 8 articles published in national journal, 2 articles published in international journal and 1 article published in proceeding of international seminar. The technique in analyzing the data used data display, data reduction and drawing conclusion. Research findings show that there are nine roles of problem based learning (PBL) in improving the learning quality at elementary schools that PBL improve learning objectives, motivation, activities, cooperation, critical thinking, problem solving ability, positive attitude and behavior, and cognitive affective and psychomotor of the students as well as the quality of learning